The regulatory niche of intestinal stem cells. (28th July 2016) - Sailaja, Badi Sri; He, Xi C.; Li, Linheng
Abstract : Constituents of the niche. The niche constitutes a unique category of cellular components (mesenchymal cells, Paneth cells, immune cells, endothelial cells, macrophages and neural cells), secreted or growth factors (R‐spondin and EGF) and BMP inhibitors (Noggin and chordin), which along with the circadian rhythms and metabolic control provide a microenvironment for the maintenance and self‐renewal of intestinal stem cells. Abstract: The niche constitutes a unique category of cells that support the microenvironment for the maintenance and self‐renewal of stem cells. Intestinal stem cells reside at the base of the crypt, which contains adjacent epithelial cells, stromal cells and smooth muscle cells, and soluble and cell‐associated growth and differentiation factors. We summarize here recent advances in our understanding of the crucial role of the niche in regulating stem cells. The stem cell niche maintains a balance among quiescence, proliferation and regeneration of intestinal stem cells after injury. Mesenchymal cells, Paneth cells, immune cells, endothelial cells and neural cells are important regulatory components that secrete niche ligands, growth factors and cytokines. Intestinal homeostasis is regulated by niche signalling pathways, specifically Wnt, bone morphogenetic protein, Notch and epidermal growth factor. These insights into the regulatory stem cell niche during homeostasis and post‐injury regeneration offer the potential to accelerate development of therapies for intestine‐related disorders.